Assembly of a Library of Pel-Oligosaccharides Featuring α-Glucosamine and α-Galactosamine Linkages - Zhang, Yongzhen; Wang, Liming; Overkleeft, Herman S.; van der Marel, Gijsbert A.; Codée, Jeroen D. C. (Frontiers in Chemistry, 2022)
Pseudomonas aeruginosa, a pathogenic Gram-negative bacterium for which currently antibiotic resistance is posing a significant problem and for which no vaccines are available, protects itself by the formation of a biofilm. The Pel polysaccharide, a cationic polymer composed of cis-linked galactosamine (GalN), N-acetyl galactosamine (GalNAc), glucosamine (GlcN) and N-acetyl glucosamine (GlcNAc) monosaccharides, is an important constituent of the biofilm. Well-defined Pel oligosaccharides will be valuable tools to probe the biosynthesis machinery of this polysaccharide and may serve as diagnostic tools or be used as components of glycoconjugate vaccines. We here, report on the development of synthetic chemistry to access well-defined Pel-oligosaccharides. The chemistry hinges on the use of di-tert-butylsilylidene protected GalN and GlcN building blocks, which allow for completely cis-selective glycosylation reactions. We show the applicability of the chemistry by the assembly of a matrix of 3x6 Pel heptasaccharides, which has been generated from a single set of suitably protected Pel heptasaccharides, in which a single glucosamine residue is incorporated and positioned at different places along the Pel oligo-galactosamine chain.